Syriac idiosyncrasies : theology and hermeneutics in early Syriac literature - Ruzer, Serge; Kofsky, Arieh (Leiden ; Boston : Brill, 2010)
The study of early Syriac Christianity has for decades been steadily expanding, yet its scope still lags way behind that of research relating to Greek and Latin Christianity. One of the intriguing and understudied topics here is the nature of Syriac Christianity's autonomous identity in late antiquity. This question is intrinsically connected to its genesis from an indigenous Christian Aramaic background as well as its interaction with the neighboring Jewish milieu. This volume unearthes some of the idiosyncracies -- mainly pertaining to trinitarian theology, christology and hermeneutics -- to.
Aphrahat : a witness of pre-Nicene Syrian theology -- Ephrem on justice, free will and divine mercy in the story of the Fall -- Liber graduum : the heavenly garden of ascetic delights -- The cave of treasures : calvary versus earthly paradise -- Philoxenus of Mabbug : hermeneutics of incarnation -- Appendix : the old Syriac gospels : textual authority and hermeneutics.
Includes bibliographical references and indexes.
Print version record.
Master record variable field(s) change: 650
Keywords: Syrian churches -- Doctrines -- History; Christian literature, Early -- Syriac authors -- History and criticism; RELIGION -- Christianity -- History; Syrian churches -- Doctrines; Electronic books; Criticism, interpretation, etc; History